2012
DOI: 10.1177/0268580911423057
|View full text |Cite
|
Sign up to set email alerts
|

Identity, diversity and citizenship: A critical analysis of textbooks and curricula in Irish schools

Abstract: Despite the long presence of migrant communities, Ireland was only transformed to a net-receiving immigration nation in 1996, and is currently experiencing net emigration in the wake of a sharp economic downturn. Debates about immigrant incorporation and educational responses are still at a relatively early stage. This study, which forms part of a larger project, set out to explore the role of schools and curricula in developing citizenship and the conception of Irish identity implicit therein. The article dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
(8 reference statements)
1
17
0
1
Order By: Relevance
“…Similar trends are also observed in Irish history textbooks following the 1996 curriculum reform, which emerges as 'a post-national document' with its redefinition of Ireland as a multicultural society (Faas and Ross 2012). Curriculum planners in Greece, too, noted the importance of addressing the issue of diversity in current Greek society (Faas 2011).…”
Section: Conceptual and Theoretical Frameworksupporting
confidence: 53%
See 3 more Smart Citations
“…Similar trends are also observed in Irish history textbooks following the 1996 curriculum reform, which emerges as 'a post-national document' with its redefinition of Ireland as a multicultural society (Faas and Ross 2012). Curriculum planners in Greece, too, noted the importance of addressing the issue of diversity in current Greek society (Faas 2011).…”
Section: Conceptual and Theoretical Frameworksupporting
confidence: 53%
“…The curriculum reform can also be seen as part of global convergence among education systems that led to the adoption of student-centred pedagogy and the need to address issues of identity and difference. It should be noted, however, that the Ministry's official statements on curriculum reform, in contrast to Greek, Irish or Korean cases as mentioned above (Faas 2011;Faas and Ross 2012;Moon 2013), did not include any explicit reference to redefining Turkey as a culturally diverse society. In other words, the official papers did not invoke any reference to recent identity-based claims to recognition as a rationale for the development of the new curriculum and textbooks.…”
Section: The Current State Of Textbooks and The Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ireland, many of those who teach CSPE have spoken about their 'lack of formal training' on how to teach the subject and how they were 'conscripted' into it (Faas and Ross 2012;Gleeson 2009). For example, a recent Irish study (Bryan and Bracken 2011, 269) concluded that 'only a very small number of the in-career teachers who participated in their study had undertaken any in-service training in the field' and also reported (2011,269) that the teachers interviewed for their study '….…”
Section: Items 2-7: Participation In Political Processesmentioning
confidence: 99%